(untitled) (New York, 1993)
The book allows us to examine the ethnic infrastructure underlying economic, social, and political change. It is essential for intelligently assessing today's multicultural news issues and becoming more aware of the cultures that surround us. The book contains more than 2.000 alphabetical entries on all peoples and ethnic groups of the world. The concise and clearly written entries are supplemented with 250 black-and-white maps and 48 pages of color illustrations. The color illustrations and photographs represent culture, costume, environment, art, architecture, and people
Keywords: Ethnic groups,Indigenous peoples; Encyclopedias,Encyclopedias